Education, inequality, and active citizenship. Tensions in a differentiated schooling system - van de Werfhorst, Herman G. (Amsterdam, 2009)
"In this essay I analyze the problems that differentiated educational systems, like the Dutch, face in preparing youth for contemporary society. I discuss the implications of three broad societal trends for education: a changing labour market, an increasing call for selection and excellence, and increasing diversity and individualization. The implications of these trends are examined for what I see as the four central tasks of education: to prepare for the labour market, to select and sort students efficiently on the basis of their capacities and interests, to promote equality of opportunity, and to prepare for active citizenship. I conclude with a description of the cheers and challenges of the Dutch educational system, leading to recommendations for Dutch educational policy."